Insulin‐like growth factor binding protein‐4 exerts antifibrotic activity by reducing levels of connective tissue growth factor and the C‐X‐C chemokine receptor 4. Issue 3 (15th January 2019) - Su, YunYun; Nishimoto, Tetsuya; Hoffman, Stanley; Nguyen, Xinh‐Xinh; Pilewski, Joseph M.; Feghali‐Bostwick, Carol
Abstract: The insulin‐like growth factor (IGF) system plays an important role in variety cellular biological functions; we previously reported levels of IGF binding proteins (IGFBP)‐3 and ‐5 are increased in dermal and pulmonary fibrosis associated with the prototypic fibrosing disease systemic sclerosis (SSc), induce extracellular matrix (ECM) production, and promote fibrosis. We sought to examine the effects of another member of the family, IGFBP‐4, on ECM production and fibrosis using cell‐based, ex vivo organ culture and in vivo mouse lung fibrosis models. IGFBP‐4 mRNA levels were significantly decreased in pulmonary fibroblasts of patients with SSc. ECM components were significantly reduced by endogenous and exogenous IGFBP‐4. IGFBP‐4 also blocked TGF‐β–induced ECM production, and inhibited ECM production ex vivo in human lung and skin in organ culture. In vivo, IGFBP‐4 reduced bleomycin‐induced collagen production and histologic evidence of fibrosis. Silencing IGFBP‐4 expression to mimic levels observed in SSc lung fibroblasts resulted in increased ECM production. IGFBP‐4 reduced mRNA and protein levels of the chemokine receptor CXCR4 and the profibrotic factor CTGF. Furthermore, CTGF silencing potentiated the antifibrotic effects of IGFBP‐4. Reduced IGFBP‐4 levels in SSc lung fibroblasts may contribute to the fibrotic phenotype via loss of IGFBP‐4 antifibrotic activity.